2008
DOI: 10.1088/1468-6996/9/3/035012
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and stabilization of Au and Au–Ag alloy nanoparticles by fungus,Fusarium semitectum

Abstract: Crystallized and spherical-shaped Au and Au-Ag alloy nanoparticles have been synthesized and stabilized using a fungus, F. semitectum in an aqueous system. Aqueous solutions of chloroaurate ions for Au and chloroaurate and Ag + ions (1 : 1 ratio) for Au-Ag alloy were treated with an extracellular filtrate of F. semitectum biomass for the formation of Au nanoparticles (AuNP) and Au-Ag alloy nanoparticles (Au-AgNP). Analysis of the feasibility of the biosynthesized nanoparticles and core-shell alloy nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(14 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The dielectric, magnetic, optical, antimicrobial, imaging, and catalytic properties of copper make this element a candidate for applications in photoelectrochemical cells, sensors, solar cells, inks, and antimicrobial coatings ( 1 , 2 ). Recent studies have also found that many microorganisms, such as bacteria ( 3 , 4 ) and fungi ( 5 ), can produce inorganic nanoparticles (NPs), such as Ag ( 6 ), Au ( 7 ), Cu ( 8 , 9 ), CuO ( 10 , 11 ), and magnetite ( 12 ), among others ( 13 ). A few studies described the synthesis of Cu NPs ( 8 , 9 ) ranging from 10 to 40 nm intra- and extracellularly by a sustainable method using bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The dielectric, magnetic, optical, antimicrobial, imaging, and catalytic properties of copper make this element a candidate for applications in photoelectrochemical cells, sensors, solar cells, inks, and antimicrobial coatings ( 1 , 2 ). Recent studies have also found that many microorganisms, such as bacteria ( 3 , 4 ) and fungi ( 5 ), can produce inorganic nanoparticles (NPs), such as Ag ( 6 ), Au ( 7 ), Cu ( 8 , 9 ), CuO ( 10 , 11 ), and magnetite ( 12 ), among others ( 13 ). A few studies described the synthesis of Cu NPs ( 8 , 9 ) ranging from 10 to 40 nm intra- and extracellularly by a sustainable method using bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The green synthesis of nanoparticles has attracted many researchers because of the high demand to produce clean, nontoxic chemicals, environmentally benign solvents, and renewable materials. Moreover, this methodology improves the biocompatibility of the obtained NPs [ 9 , 10 , 11 ]. For instance, many successful attempts have been reported in the literature, which achieve the synthesis of nanoparticles using biological systems, such as yeast, fungi, and bacteria [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioreduction of gold ions by biomolecules in plant leaf extracts are the likely reason for this observation [33,34]. FT-IR spectra with an analysis of vibrations is a suitable means for measuring minor structures in interactions between metallic nanoparticles and biomolecules [35]. Figure 4 showed that the N–H bonding vibration of leading amines and C–N elongation and coincidence of aliphatic amines have the robust capability to bind metal; hence, the phytochemicals from the plant extract putatively make a coating that shields the metal nanoparticles.…”
Section: Discussionmentioning
confidence: 99%